Development of Picture Story Media with Articulate Storyline 3-Based Smart Quiz in Fable Stories in Grade II Elementary School - Asmi, Asfari Mahiruddin; Mudiono, Alif; Muzaki, Ferril Irham (Journal of Education for Sustainability and Diversity, 2024)
This research and development was made with the aim of developing picture story media with Articulate Storyline 3-based shortcut quizzes that are valid, interesting, and practical. Valid media based on material experts, media experts, and users (teachers) as well as practical and interesting media for second grade students of SD Negeri 2 Sengon. The model used is the ADDIE model with five stages including: analysis (analyze), design (design), development (develop), implementation (implement), and evaluation (evaluate). Data collection techniques in this research and development use observation, interviews, and questionnaires. This media obtained material expert validation results of 92.85%, media expert validation results of 88.09%, and user validation results of 94.28%, attractiveness results of 98.95%, and practicality results of 98.10%. Based on the results of media validation, it is classified as very valid and can be used without revision, while based on the results of the attractiveness and practicality of the media it is classified as very attractive and very practical and can be used without revision.